A Moderating Effect of Profitability: Empirical Studi in Minning Industry - Akhmadi Akhmadi; Randy Joy Vantayen (International Business and Accounting Research Journal, 2023)
This study aims to examine the impact of profitability on firm value in mining sector firms from 2009 to 2020. Data were collected from 12 years' worth of observational data from 19 companies, resulting in 228 data points across 51 populations. The collected data were analyzed using various methods such as descriptive analysis, conventional assumption testing, and hypothesis testing. The findings indicate that Firm Value is not significantly influenced by Firm Size, despite the potential for profitability to strengthen the association between its size and value.